THYROIDITIS DUE TO INFILTRATION OF ANTERIOR MEDIASTINAL HODGKIN’S LYMPHOMA: A CASE REPORT - Jalal, Fadzliana Hanum; Jusoh, Faiz; Ibrahim, Luqman; Lim, Quan-Hziung; Ratnasingam, Jeyakantha; Vethakkan, Shireene Ratna; Lim, Lee-Ling; Paramasivam, Sharmila Sunita (Journal of the ASEAN Federation of Endocrine Societies, 2021)
INTRODUCTION Hodgkin’s lymphoma is the most common type of lymphoma arising from the anterior mediastinum that may extend to the pre-tracheal region. Infiltration of non-thyroid malignancies (including hematological) into the thyroid gland is not common but has been described and may result in thyroid dysfunction. RESULTS We present a case of a 28-year-old woman with no prior medical illness who presented with a 2-month history of chest discomfort and shortness of breath associated with new onset anterior neck swelling. She had occasional palpitations but did not have other symptoms of hyperthyroidism. There was no family history of thyroid disease. On examination, she was tachypnoiec with an audible stridor at rest and a heart rate of 142 bpm.There were no tremors, proximal myopathy, hyperreflexia or exophthalmos. She had a large non-tender asymmetrical anterior neck mass, which was hard, matted and did not move with swallowing. Thyroid function tests showed freeT4: 26.7 pmol/L[11.5-22.7], T3: 6.12 pmol/L [3.93-7.2] and TSH:0.04 mIU/L [0.550- 4.78]. Anti-TG, Anti-TPO, thyroid-stimulating immunoglobulin (TSI) levels were normal. ECG showed sinus tachycardia. CT thorax/ abdomen/pelvis revealed bilateral supraclavicular lymph nodes and large matted masses in the anterior mediastinum invading the lower lobes of the thyroid, with the gland itself being normal. Her heart rate normalized with hydration and propranolol. She was also treated with high dose IV dexamethasone for the upper airway obstruction. The neck mass decreased in size with dexamethasone and her thyroid function tests normalized within a month without antithyroid medications. Histopathological examination confirmed Hodgkin’s lymphoma and she was commenced on chemotherapy. CONCLUSION Anterior mediastinal Hodgkin’s lymphoma may infiltrate into the thyroid gland causing thyroiditis. Treatment of the underlying malignancy may result in complete recovery of the thyroid in some cases. Hyperthyroid symptoms may be treated with betablockers alone, and anti-thyroid drugs are usually not warranted.